On H1-compositors and piecewise continuous mappings (in Ukrainian) - O. V. Sobchuk; O. O. Karlova (Математичні Студії)
We introduce the notion of a right $H_1$-compositor and provethat for a hereditarily Baire metrizable space $X$, a normalspace $Y$ and a mapping $fcolon Xo Y$ the followingconditions are equivalent: (i) $f$ is piecewise continuous;(ii) $f$ is $k$-continuous; (iii) $f$ is $G_delta$-measurable;if, moreover, $Y$ is perfect, then (i)--(iii) are equivalentto: (iv) $f$ is a right $H_1$-compositor.